Management and clinical outcome of rectal cancer in patients ≥80 years treated in southern France (PACA region) between 2006 and 2008. Issue 7 (20th September 2013) - Moureau‐Zabotto, L.; Resbeut, M.; Gal, J.; Mineur, L.; Teissier, E.; Hebuterne, X.; Muyldermans, P.; Francois, E.; Chamorey, E.; Gerard, J‐P
Abstract Background Rectal cancer is increasingly prevalent in the elderly patients. Their clinical history and outcome after treatment are poorly described. This retrospective study was undertaken to provide more data and to compare therapeutic strategies to the standard of care for younger patients. Patients and Methods Data were retrospectively provided by gastroenterologists, oncologists, and gerontologists of Provence‐Alpes‐Côte‐d'Azur (PACA). Patients concerned were aged 80 years or older, with a rectal cancer diagnosed between 2006 and 2008, irrespective of stage and (the) treatment of the disease. Overall survival (OS) and relapse‐free‐survival (RFS) were correlated with patient characteristics and treatment. The adopted therapeutic strategy was then compared to the standard‐of‐care for younger patients. Results Median follow‐up was 36 months. The 3‐year OS was 47.4% for the 160 patients analyzed, and 59.2% for the 117 patients treated with curative intent. The 3‐year RFS was 76.6% in the "curative" population. In the multivariate analysis, node status and surgery independently influenced OS, while RFS was influenced by age, N status, and gender. For T0–T2 tumors, patients were treated similar to younger patients with an OS of 83.6% and a RFS of 95.2%, respectively. For T3–T4 tumors, 3‐year RFS was 65%, even with a less aggressive strategy. Conclusion Surgical resection after evaluation using Comprehensive Geriatric Assessment (CGA) should be the standard treatment for localized rectal cancer (T0–T2) in elderly patients, as it is in younger patients. For locally advanced lesions (T3–T4), results obtained after a conservative approach suggest that a non‐surgical strategy can be used in elderly patients. J. Surg. Oncol. 2013; 108:450–456. © 2013 Wiley Periodicals, Inc.